Adipose-Derived Stem Cell Therapies In Radiation-Induced Soft-Tissue Damage: A Comprehensive Systematic Review - Dandoulakis, MD, Emmanouil (Journal of Neonatal Surgery, 2025)
Radiation induces soft-tissue injury, which is a valuable side effect of cancer treatment. It causes fibrosis, ulceration, and delayed wound healing, significantly impairing the quality of life for patients. Adipose-derived stem cells (ADSCs) are promising as therapeutic agents that can repair tissues. They are beneficial because they can differentiate into various cell types, are readily obtainable, and release potent signals that promote healing. This review examines the efficacy of ADSC-based therapy in treating radiation-induced soft tissue injuries. It integrates evidence from case series and laboratory studies with a discussion of developing treatment methods. ADSCs can remodel tissues by promoting fat cell proliferation, creating connective tissue, forming blood vessel cells, and regulating immune responses. ADSCs also release VEGF, HGF, and IL-10 growth factors that inhibit inflammation and scarring. New therapies comprise exosome-based repair through microRNAs (e.g., miR-21, miR-146a) to modulate the activity of fibroblasts, the transfer of mitochondria to reestablish cellular bioenergetics, epigenetic reprogramming to reverse cellular senescence, and nanoparticle-mediated delivery of ADSC to enhance specificity in irradiated tissues. Preclinical research suggests that increased wound healing, reduced fibrosis, and decreased angiogenesis may be achieved. Clinical trials have demonstrated improved skin integrity, reduced lymphedema, and a favorable safety profile with minimal side effects. The challenges are that standardized protocols and larger clinical trials should be conducted to guarantee scalability and long-term safety. A combination of advanced delivery systems (microneedle patches and bioactive scaffolds) with AI-based optimization promises to revolutionize post-radiation care and provide regrowth-based solutions tailored to the individual, offering an expertly fine-tuned, regenerative therapy that has the potential to significantly improve the current management of radiation-induced soft-tissue damage, thereby vastly enhancing clinical outcomes..